Defining concepts of the digital society - Christian Katzenbach; Thomas Christian Bächle (Internet Policy Review, 2019)
At a time when branding new, occasionally innovative but often only catchy terms has become a familiar activity of researchers, companies and policymakers alike, it is necessary to reflect on which of these concepts is actually worthwhile, provides analytic value and in effect describes something new. This new special section Defining concepts of the digital society seeks to foster a platform that discusses and validates these overarching frameworks and theories. Based on the latest research, yet broad in scope, the contributions offer effective tools to analyse the digital society. Their authors offer concise articles that portray and critically discuss individual concepts such as algorithmic governance, datafication, platformisation, privacy with an interdisciplinary mindset. Each article contextualises their respective origin and academic traditions, analyses their contemporary usage in different research approaches and discusses their social, political, cultural, ethical or economic relevance and impact as well as their analytical value. The special section is a continuing project that will expand the collection of concepts in 2020 and beyond. We sincerely hope that it will grow into a valuable forum for making sense of the digital transformation and a pertinent resource for researchers, teachers, students and practitioners.
Keywords: 300; Digital society